Keuntungan Industri Rumah Tangga Usaha Pengolahan Tahu Di Kelurahan Karombasan Utara Lingkungan I Kecamatan Wanea Kota Manado (Studi Kasus Pada Pengolahan Tahu Bapak Gendon) - Matasak, Josua; Sendow, Martha Mareyke; Montolalu, Maya Hendrietta (Sam Ratulangi University, 2023)
This study aims to determine the profit of Mr. Gendon's tofu processing business in Karombasan Utara Village, Ward 1, Wanea District, Manado City. This research will be carried out for three months from May to July 2023. This research took place at Mr. Gendon's tofu processing business in Karombasan Utara sub-district, Ward 1, Wanea District, Manado City. The research method is a case study. The data used in this study are primary data and secondary data. Primary data was obtained by using interview techniques directly to the owner of the tofu processing business, Mr. Gendon, by using a questionnaire as a data collection tool and filled in by the researcher. Secondary data in this study came from bookkeeping records of tofu processing businesses. The results of the study showed the profit of Mr. Gendon's tofu processing business in Karombasan Utara Village, Ward 1 Wanea District, Manado City can be said to be profitable with a total profit of IDR38.534.375 per month with a total cost of IDR97.545.625 per month and total revenue of IDR136.080.000 per month.